Aquatic chemistry : chemical equilibria and rates in natural waters - Stumm, Werner, 1924-; Morgan, James J., 1932- (New York : Wiley, 1996)
Like the previous editions, this substantially revised and updated Third Edition has been written to provide readers with a solid understanding of the general chemical principles underlying natural water chemistry: chemical thermodynamics and kinetics, acids and bases, dissolved carbon dioxide, atmosphere-water interactions, metal ions in aqueous solutions, precipitation and dissolution, oxidation and reduction, equilibria, and the solid-solution interface.
To help the reader grasp the essential elements of aquatic chemistry, the authors illustrate key principles with numerous quantitative examples and a full range of problem-solving methods, including algebraic, graphical, and numerical methods based on digital computation. Designed for both reference as well as classroom use, Aquatic Chemistry, in this new edition, remains the authoritative resource on the fundamentals of natural water chemistry.
1. Introduction -- 2. Chemical Thermodynamics and Kinetics -- 3. Acids and Bases -- 4. Dissolved Carbon Dioxide -- 5. Atmosphere-Water Interactions -- 6. Metal Ions in Aqueous Solution: Aspects of Coordination Chemistry -- 7. Precipitation and Dissolution -- 8. Oxidation and Reduction; Equilibria and Microbial Mediation -- 9. The Solid-Solution Interface -- 10. Trace Metals: Cycling, Regulation, and Biological Role -- 11. Kinetics of Redox Processes -- 12. Photochemical Processes -- 13. Kinetics at the Solid-Water Interface: Adsorption, Dissolution of Minerals, Nucleation, and Crystal Growth -- 14. Particle-Particle Interaction: Colloids, Coagulation, and Filtration -- 15. Regulation of the Chemical Composition of Natural Waters -- Appendixes: Thermodynamic Data.
"A Wiley-Interscience publication."
Includes bibliographical references and index.
Keywords: Water chemistry